Non-traumatic subdural hematoma in patients on maintenance hemodialysis: A 10 year audit of a hemodialysis facility in Cameroon - Ashuntantang, Gloria E.; Kaze, Francois F.; Halle, Marie-Patrice; Menanga, Alain P.; Tatah, Godwin; Ze Minkande, Jacqueline; Njamnshi, Alfred K.; Eyenga, Victor C. (HEALTH SCIENCES AND DISEASE, 2014)
ABSTRACT Introduction: Non-traumatic subdural hematoma (SDH) is a rare but grave complication of hemodialysis (HD). Recent data suggests the annual incidence has doubled in the last decade in the USA. With geographic variations in epidemiologic profile of the maintenance HD population, we sought to study the pattern of non-traumatic SDH in a Sub-Saharan African hemodialysis setting. Methodology We conducted a retrospective review of medical records of patients treated by maintenance hemodialysis diagnosed by brain CT scan at the Hemodialysis unit of the Yaoundé General Hospital from November 2002 to November 2012 to identify patients with non-traumatic subdural hematoma occurring after a period of at least 90 days on maintenance HD. Relevant data was collected for analysis. Results A total of two cases of non-traumatic SDH were identified from the 464 patient records (cumulative incidence of 0.43% in 10 years). These were males with end stage renal disease from malignant nephrosclerosis. The mean age was 52 years. None was receiving prophylactic anti-thrombotic agents. Headaches and neurological deficits were the main clinical features. Treatment was surgical with a mortality rate of 50%. Large interdialytic weight gain, excessive ultrafiltrates and uncontrolled hypertension were common findings. Conclusion The frequency, clinical presentation, and prognosis of non-traumatic SDH are similar to studies in Europe and the USA. However, contrary to the later, non-traumatic SDH occurs in young males not on prophylactic antithrombotic agents in our setting. Early diagnosis through a high index of suspicion and access to CT scan may reduce diagnostic delays and improve outcome. Key words: non-traumatic subdural hematoma, hemodialysis, management, outcome RESUME Introduction L’hématome sous-dural (HSD) non-traumatique est une complication rare et grave de l’hémodialyse chronique (HDC). Les données récentes suggèrent que l’incidence annuelle a doublé au cours de la dernière décennie aux Etats Unis. Avec la différence des caractéristiques des hémodialysés chroniques, nous avons entrepris d’étudier le profil de l’HSD non-traumatique en Afrique Sub-Saharienne. Méthodologie Il s’agissait d’une analyse rétrospective des dossiers médicaux d’hémodialysés chroniques depuis au moins trois mois, ayant présenté un HSD non-traumatique diagnostiqué au scanner cérébral dans l’unité d’hémodialyse de l’Hôpital Général de Yaoundé pendant la période allant de Novembre 2002 à Novembre 2012. Les données cliniques importantes étaient relevées. Résultats Sur 464 dossiers médicaux recensés, deux cas d’HSD non-traumatique ont été identifiés, soit une incidence cumulative de 0,43% en 10 ans. Il s’agissait des sujets de sexe masculin, d’âge moyen de 52 ans, en insuffisance rénale chronique terminale secondaire à une hypertension artérielle maligne, ne recevant aucune prophylaxie anti-thrombotique et présentant des céphalées associées aux déficits neurologiques. Le traitement était chirurgical avec un taux mortalité de 50%. La prise importante de poids interdialytique, l’ultrafiltration excessive et l’hypertension artérielle non contrôlée étaient les principales trouvailles cliniques. Conclusion La fréquence, la présentation clinique et le pronostic de l’HSD non-traumatique reportés dans cette étude sont similaires aux données européennes et américaines. Cependant, dans notre série, HSD non-traumatique survient chez des sujets jeunes, en absence de traitement anti-thrombotique prophylactique. Le diagnostic précoce par une suspicion clinique et l’accès au scanner cérébral pourraient améliorer leur pronostic. Mots clés : hématome sous-dural non-traumatique, hémodialyse, traitement, pronostic.